Prevalence of adverse childhood experiences and their association with suicidal ideation and non-suicidal self-injury among incarcerated methamphetamine users in Japan. (September 2022) - Takahashi, Masaru; Yamaki, Mayuko; Kondo, Ayumi; Hattori, Masato; Kobayashi, Michiko; Shimane, Takuya
Abstract: Background: Adverse childhood experiences (ACEs) are distressing and/or traumatic events that occur during childhood that increase the risk of negative health outcomes in adulthood. Objective: This study estimated the prevalence of ACEs in a nationwide sample of Japanese methamphetamine users in prison and examined associations among ACEs, suicidal ideation, and non-suicidal self-injury. Participants and setting: Participants were 636 inmates (418 male and 218 female) who were newly incarcerated in Japan for Stimulants Control Act violations. Methods: First, 699 participants completed an anonymous self-report questionnaire. Of these, 636 participants who did not have any missing responses were included in the analysis. After calculating descriptive statistics, the associations between ACEs and suicidal behaviors were assessed using binary logistic regression analyses. Results: Results showed that 76.1 % of the participants reported at least one ACE before the age of 18, and female participants reported a significantly higher number of adversities than their male counterparts. The most common ACEs were parental death or divorce, followed by psychological abuse. Logistic regression analyses revealed that ACE scores significantly increased the risk of suicidal ideation (SI; adjusted odd ratio [AOR] = 1.18, p < .001) and non-suicidal self-injury (NSSI; AOR = 1.18, p < .001) after controlling for possible confounding variables. Conclusions: Findings suggest the importance of early prevention and intervention for traumatic experiences, and have implications for the recommendation of gender-responsive, trauma-focused interventions, especially for female inmates in the criminal justice system, to break the intergenerational chain of abuse. Future research directions and treatment are discussed.